Hubungan interdialytic weight gain (IDWG) dengan tekanan darah intradialitik pada pasien yang menjalani hemodialisis - Rindang Isnenti; Lia Novianty; Astri Zeini Wahida (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Chronic kidney disease (CKD) is a global health problem requiring lifelong hemodialysis therapy. Excessive fluid accumulation between dialysis sessions, or Interdialysis Weight Gain (IDWG), poses a clinical challenge because it directly affects hemodynamic stability, particularly intradialysis blood pressure fluctuations. Purpose: To analyze the relationship between Interdialysis Weight Gain (IDWG) and intradialysis blood pressure in patients with chronic kidney disease. Method: This quantitative, observational, and analytical study involved 136 respondents at Sekarwangi Regional Hospital, selected using a total sampling technique. IDWG and blood pressure data were collected through direct observation during two hemodialysis sessions. Data were analyzed using the Chi-Square test with Continuity Correction (Yates). Results: This study found that 67.6% of respondents had severe IDWG (>3%), and 57.4% had intradialysis hypertension. Bivariate analysis showed a significant association between IDWG and intradialysis blood pressure (p = 0.000). Conclusion: There is a significant relationship between interdialysis weight gain (IDWG) and intradialysis blood pressure in patients with chronic kidney disease undergoing hemodialysis. Keywords: Chronic Kidney Disease; Hemodialysis; Intradialysis Blood Pressure; Interdialysis Weight Gain (IDWG).